INVESTIGATING INDONESIAN EFL TEACHERS’ PERCEPTIONS ON THEIR SELF-EFFICACY - Kristian Florensio Wijaya (Universitas Islam Negeri Alauddin Makassar, 2022)
To fully arm Indonesian EFL educationalists with a higher degree of professionalism, tenacity, and optimism in confronting ever-changing ELT landscapes, self-efficacy is one of the pivotal psychological streams that should be strong-inherited within them before plunging into real-time language learning contexts. This present study attempted to investigate the specific perceptions upholding by Indonesian EFL teachers toward their self-efficacy growth amid varied language learning dynamics they constantly endure. This study was run in the fashion of qualitative method to obtain more comprehensive data out of the particular phenomenon experienced by research participants. To fulfill this major research objectivity, the researcher capitalized on 5 open-ended written narrative inquiries to gain some renewable insights from the invited research participants. 2 Indonesian EFL teachers possessing a distinctive length of teaching experiences were invited to take part in answering the aforesaid 5 open-ended written narrative inquiry questions through WhatsApp application. More specifically, these 2 invited Indonesian EFL teachers enrolling in the English Education Master Program of Sanata Dharma University, Yogyakarta. The obtained research results uncovered that the robust establishment of self-efficacy was strongly affected by varied external factors such as a higher degree of learners’ learning endeavor and intensive professional development training addressed by educational institutions, which in turn transforming them into more professional educators. As a suggestive point, all educational parties in this archipelago were strongly advocated to design continual professional development programs heeding more profound attention in corroborating our EFL teachers’ self-efficacy levels for the advancement of ELT venture thoroughly. Keywords: EFL teachers’ perceptions, self-efficacy, narrative inquiry